Nanotechnology-based advancements for effective delivery of phytoconstituents for Ocular diseases - Venkateshwaran Krishnaswami; Dhilin Pathayappurakkal Mohanan; S.A. Jacob Raja; Balakrishnan Natarajan; Shankarananth Velusamy (Nano TransMed)
Phytomedicines has been globally utilized in ancient times. Phytoconstituents such as flavonoids, glycosides, peptides, carbohydrates, lipids, alkaloids, tannins, and terpenoids are holding medicinal properties. Previous reports have documented the various therapeutic activities of plant extracts/isolated fractions/pure phytoconstituents especially at in vitro levels. But the relevance towards the in vivo level and upmost towards the clinical trials for these phytomedicines was facing numerous challenges in the current scenario. The challenges associated with phytomedicines are standardization issues, ineffective against serious ailments, poor reproducibility of biological activities and interferences with associated phytoconstituents. But recently nanoscale based phytomedicine is paving more interest towards the scientific community for ocular delivery. In order to overcome these issues the nanoscale base phytomedicines delivery systems are recently developed by researchers. Nanoscale delivery systems of various phytoconstituents may potentiate the therapeutic effect, improves the bioavailability, reduces adverse effects and decreases the effective dose. The scope of this paper will focus towards the nanotechnology based phytomedicine delivery systems for various therapeutic applications in eye. The various phytomedicine loaded nanoscale delivery systems such as nanoparticles, nanomicelles, nanodispersions, lipid based nanoparticles for various ocular diseases has been reviewed. Special focus has been emphasized towards the carriers utilized for those delivery systems. Additionally, the future perspectives relating to development of novel phytomedicine based nano formulations has been discussed.